The Effectiveness of Teaching Mathematics Using Fun Learning Strategies in Developing Productive Mathematical Dispositions Among Tenth Grade Female Students in the Sultanate of Oman - Al-Mukhini, Wedad Rajab Rabee; Al-Shannaq, Mamoon Mohammad (Dirasat: Educational Sciences, 2024)
Objectives: The study aimed to investigate the effectiveness of teaching using fun learning strategies in developing productive mathematical disposition among tenth-grade female students in the Sultanate of Oman. Methods: A quasi-experimental design was employed. The study sample comprised 200 tenth-grade female students divided into two groups: an experimental group of 98 students taught using fun learning strategies, and a control group of 102 students taught in the traditional manner. The study utilized a productive mathematical disposition scale consisting of 15 items across four components to measure outcomes. The validity and reliability of the instrument were confirmed using appropriate methods. Results: The results indicated statistically significant differences (α =.05) in the productive mathematical disposition scale as a whole and in each of its components, favoring the experimental group. Conclusion: Based on these findings, the study recommends integrating fun learning strategies into educational practices. It also suggests further research to explore the effectiveness of fun learning strategies across different variables, grade levels, and mathematical topics.